PENGARUH KUALITAS LAYANAN, PROMOSI PENJUALAN DAN DIGITAL MARKETING TERHADAP LOYALITAS KONSUMEN GOJEK DI DENPASAR - Hanjaya, Jaka Kusuma; Setiawan, Putu Yudi (E-Jurnal Manajemen; Vol 11 No 9 (2022)DO - 10.24843/EJMUNUD.2022.v11.i09.p03, 2022)
Consumer loyalty is the willingness of customers to always use the company's products in the long term, use exclusively, and recommend the company's products to friends or colleagues. The purpose of this study is to determine the effect of service quality on loyalty consumer, the sales promotion on loyalty consumer, digital marketing on loyalty consumer. The sample in this study is customers of Gojek in Denpasar City. Determination of the sample in this study using non-probability sampling method. The number of samples taken as many as 112 people. Analytical techniques used is analysis of multiple linear regression. The findings of this study indicate that there is a positive and significant relationship between service quality with loyalty consumer, sales promotion with loyalty consumer, digital marketing with loyalty consumer. These results practically it can be reference for other people who want to research about service quality, sales promotion, digital marketing, and consumer loyalty. Keywords: service quality, sales promotion, digital marketing, loyalty consumer